I love you, Bingo - Soman, David; Davis, Jacky, 1966- (Soman, David. Ladybug Girl (Series), 2015)
Lulu loves being ladybug girl. She loves her dog, Bingo, too. Every day they play together. They fly and run and jump. And ladybug girl always remembers to tell Bingo that she loves him!